A literary history of England Vol.3 : The Restoration and eighteenth century (1660-1789) - Sherburne, George . (Routledge, 1967)
English historians in the Middle Ages is an overview of the history of English historians and their works in the Middle Ages. English historians helped lay the groundwork for modern historical methodology, provided vital accounts of the early history of England, its culture, and revelations about the historians themselves. The most remarkable period of historical writting was during the High Middle Ages in the 12th and 13th centuries, when English chronicles produced works with a variety of interest, wealth of information and amplitude of range. However one might choose to view the reliability.